The effect of γ′ and δ phases evolution on the mechanical properties of high-entropy CoCu0.5FeNiTa0.1 alloy during heat treatment - Zhengyuan Yuan; Min Zhang; Zhunli Tan; Wenbo Yu (Journal of Materials Research and Technology)
To simultaneously improve the mechanical strength and plasticity of the CoCu0.5FeNiTa0.1 high entropy alloy, we adopted the heat treatment and investigated the evolution of different phases containing γ′, δ and γ phases. Two different γ′ phases, the Cu-rich phase and the Ta-rich phase, were detected in the as-cast alloy. During heat treatment, Cu outwards diffused from γ′(Cu-rich) into γ matrix, γ′(Ta-rich) phase and δ phase. The accumulation of Cu and Ta into the δ phase strongly promoted its growth. One significant increase was measured in the compressive yield strength from 1040 MPa to 1370 MPa, ultimate compressive strength from 2020 MPa to 2735 MPa, compressive strain from 34% to 50.2% and hardness from 3.854 GPa to 4.315 GPa. The substantial enhancement in ductility mainly resulted from the distance increase among γ′ particles in γ matrix, the reduction of lattice distortion and the decrease in aspect ratio of δ phases. The yield strengthening mechanisms were mainly from solid strengthening and Orowan strengthening.